Development of an instrument to evaluate diagnosis accuracy - Matos, Fabiana Gonçalves de Oliveira Azevedo; Cruz, Diná de Almeida Lopes Monteiro da (Revista da Escola de Enfermagem da USP, 2009)
Accurate diagnoses are important for choosing adequate interventions. This study reports on a methodological research that developed an instrument to estimate nursing diagnosis accuracy, based on written data from patients' assessment. A definition of accuracy was elaborated and the items that compose the instrument were constructed and submitted to content validation and pilot test. The instrument was named Nursing Diagnosis Accuracy Scale - NDAS and comprised four items: Presence of cues; Relevance of cues; Specificity and Coherence of cues. The answers of 12 expert nurses regarding the application of NDAS to the diagnoses of five written cases permitted the identification of values for each item and estimation of validity and reliability of the NDAS.